Patient safety and quality improvements in parotid surgery. Issue 2 (27th April 2022) - Talati, Vidit; Brown, Hannah J.; Losenegger, Tasher; Revenaugh, Peter; Al‐Khudari, Samer
Abstract: Parotidectomy is the mainstay treatment for tumors of the parotid gland. In an effort to improve clinical outcomes, several modern surgical techniques and perioperative interventions have been evaluated and refined. This review discusses current and actively debated perioperative interventions aimed at improving patient safety and the quality of parotidectomy. Relevant high‐impact literature pertaining to preoperative diagnostic modalities, intraoperative surgical techniques, and postoperative care will be described. Key points: Fine needle aspiration is a suitable diagnostic modality for parotid tumors but has important limitations. Extracapsular dissection is safe and effective for small superficial tumors away from the facial nerve. Nerve monitoring may reduce temporary facial weakness but does not replace robust surgical technique. Outpatient parotidectomy is safe and feasible for appropriately selected patients.